¹H NMR handbook of natural products. - Qin, Hailin (Biochemist) (De Gruyter ; Chemistry Industry Press, 2021)
This 6 volume set presents a groundbreaking resource in this branch of natural organic compounds and demonstrates how proton nuclear magnetic resonance (NMR) spectroscopy can be manipulated in structures of natural organic compounds. The authors provide the most comprehensive data of 17 kinds amounting to over 10,000 natural organic compounds. The 1st volume mainly illustrates the molecular formula and structures of alkaloids.